Bharatiya Sakshya Adhiniyam, 2023 (evidence): a commentary - Verma, J. K. (Lucknow Eastern Book, 2024)
Bharatiya Sakshya Adhiniyam, 2023 (Evidence): A commentary by J.K. Verma is a treatise on the newly enacted Bharatiya Sakshya Adhiniyam, 2023 (BSA), which repealed and replaced the Indian Evidence Act, 1872. Since significant sociological and scientific developments have taken place since independence, the provisions of the Act of 1872 increasingly required a thorough overhaul to incorporate these advancements. The result is the present Bharatiya Sakshya Adhiniyam, 2023.
Keywords: New law; Bharatiya Sakshya Adhiniyam 2023